Application of Social Cognitive Career Theory in Various Studies - Rezky, Muhammad Iqbal; Rasto, Rasto (Universitas Muhammadiyah Metro, 2024)
This study conducted a bibliometric analysis of the application of Social Cognitive Career Theory (SCCT) in various studies to understand research trends, research subjects, influential publications, prolific authors, geographical distribution, and keywords often appearing in SCCT literature. The research method used was bibliometric analysis with VosViewer software. Data were collected from the Scopus database using the PRISMA2020 protocol. The analysis results show that interest in SCCT continues to increase, with peak publications in 2022. SCCT has been applied in various research fields, including Social Sciences, Psychology, Business, Management, and Accounting. Influential articles in the SCCT literature have expanded the understanding of SCCT applications in the context of career decision-making. Prolific authors related to SCCT are Lent, R.W, Brown, S.D, and Dos Santos, L.M. Geographically, the United States dominates the number of publications, but global interest in SCCT is evident from the contributions of countries such as China, South Korea, and Australia. Keywords that frequently appear in the SCCT literature include